Teratoglaea hohuanshanensis sp. nov., a new Xylenini moth endemic to Taiwan (Lepidoptera, Noctuidae, Noctuinae) - Wu, Shipher (Zootaxa, 2013)
Teratoglaea Sugi, 1958 is a peculiar noctuid genus and has long been considered to contain only one rare species, pacifica Sugi, 1958, ranging through the Manchurian-Pacific area of the north-eastern Palaearctic region (Japan, Korea, N. E. China, South of Russian Far East)(Sugi 1958; 1982; Kononenko et al. 1998; Chen, 1999; Kononenko 2005; Eda and Shikata 2011) and subtropical alpine Taiwan (Hreblay and Ronkay 1997). The peculiar large scale tufts on the metathorax and incised forewing costal margin at 3/4 of the length from the base have defined its unique generic status (Sugi 1958). According to the biology and genital structures (i.e. the late autumnal appearance of adults, overwintering then flying again in spring) and the armature of vesica with one long cornutus situated on the apical part of the vesica, Fibiger and Hacker (2007) placed this genus into Xylenini, Xyleninae (currently Noctuinae sensu Zahiri et al. 2013) and embedded this genus in subtribe Xylenina; however the absence of the digitus is discordant with most of the other included genera.